2018
DOI: 10.1186/s13075-018-1534-y
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TGF-β/Smad signaling by the small compound HPH-15 ameliorates experimental skin fibrosis

Abstract: BackgroundTransforming growth factor-β (TGF-β)/Smad signaling is well known to play a critical role in the pathogenesis of systemic sclerosis (SSc). We previously developed an artificial molecule, the histidine-pyridine-histidine ligand derivative HPH-15, which may have an antifibrotic effect. The purpose of the present study was to clarify the effects of this drug in human skin fibroblasts and in a preclinical model of SSc.MethodsThe effects of HPH-15 on expression of extracellular matrix components and TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Blocking TGF-β/Smad signaling has become a hot spot to inhibit or even reverse fibrosis. It has been reported that silencing Smad 2/3 could block Smad signaling and reduce collagen synthesis and proliferation of fibroblasts[ 40 , 41 ]. We silenced the expression of p-Smad2/3 and explored the role of Smad2/3 in TGF-β1-treated IEC-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking TGF-β/Smad signaling has become a hot spot to inhibit or even reverse fibrosis. It has been reported that silencing Smad 2/3 could block Smad signaling and reduce collagen synthesis and proliferation of fibroblasts[ 40 , 41 ]. We silenced the expression of p-Smad2/3 and explored the role of Smad2/3 in TGF-β1-treated IEC-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β-induced EMT is mainly mediated by the SMAD pathway, and activated TβR-I can specifically recognize and bind to Smad2 and Smad3. Smad2/Smad3 plays an important role in the biological effects of TGF-β, as it is the first signaling molecule for TGF-β pathway-mediated activation [29][30] . There are five binding sites in the promoter region of NRP1 for transcription factor SMAD3 have been predicted using bioinformatics software.…”
Section: Discussionmentioning
confidence: 99%
“…Ly6‐C high inflammatory monocytes respond to inflammatory signals and leave the circulation by extravasation, whereas Ly6‐C low monocytes patrol the luminal side of the vasculature. Recent studies have demonstrated that Ly6‐C high inflammatory monocytes are increased in the tissues in mouse models of fibrosis, including lung fibrosis, unilateral ureteral obstruction–induced fibrosis, and bleomycin‐induced skin fibrosis . Depending on the specific cytokines to which they are exposed, tissue Ly6‐C high macrophages down‐regulate Ly‐6C and polarize cells into tissue‐remodeling/profibrotic (M2‐like) macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Female C57BL/6 wild‐type mice (CLEA Japan), BALB/c wild‐type mice, and CX 3 CR1 −/− mice (on a BALB/c background) ages 8–10 weeks were used in the experiments. As described in our previous study , we performed 2 different experiments using a bleomycin‐induced skin fibrosis model in C57BL/6 wild‐type mice. In the preventive experiment, bleomycin (150 μg) was injected subcutaneously once daily into the shaved backs of the mice, concurrent with intraperitoneal injection of the neutralizing anti‐mouse CX 3 CL1 mAb or control IgG at a dose of 500 μg twice a week.…”
Section: Methodsmentioning
confidence: 99%